Transcriptoma e peptidoma de tentáculos de Bunodosoma caissarum CORRÊA, 1964 - Mazzi, Maria Eduarda Esquinca [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The marine environment is extremely diverse and has about 50% of the planet's species, which developed adaptive mechanisms that ensure their survival in the seas and oceans. These mechanisms occur at a morphological, physiological, behavioral and/or biochemical level, where one of the strategies used by animals is the production of poison that helps in defense or obtaining food. This secretion is loaded with biologically active molecules, such as proteins, peptides, salts and polyamines, which may have therapeutic potential. Among these molecules are peptides, amino acid sequences of up to 10 kDa that have a variety of functions and can act as regulatory molecules in cardiovascular, neurodegenerative, inflammatory and immunological diseases. Among the marine groups that produce venom are the cnidarians, releasing it through structures known as cnidocytes. In this context, this project used next generation sequencing and mass spectrometry to characterize transcripts and peptides from a marine anemone species widely distributed along the Brazilian coast: Bunodosoma caissarum (B. caissarum). The transcriptome analysis resulted in the annotation of 23,444 genes, of which 48 toxins produced by species belonging to the cnidarians were identified. Additionally, 15 of these toxins were confirmed by mucus proteomics experiments, three of which were previously described in B. caissarum. The transcriptome integrated to mass spectrometry data resulted in the identification of 2102 peptide sequences. Therefore, this study enriched the database of species, an initial step for future investigation of molecules with pharmacological potential.

O ambiente marinho é extremamente diverso e possui cerca de 50% das espécies do Planeta, as quais apresentam mecanismos adaptativos às características dos mares e oceanos para garantir sua sobrevivência. Estes mecanismos ocorrem em nível morfológico, fisiológico, comportamental e/ou bioquímico, onde uma das estratégias utilizadas pelos animais é a produção de peçonha que auxilia na defesa ou obtenção de alimento. Essa secreção é carregada de moléculas biologicamente ativas, como proteínas, peptídeos, sais e poliaminas, que podem apresentar potencial terapêutico. Dentre estas moléculas estão os peptídeos, sequências de aminoácidos de até 10 kDa que possuem uma diversidade de funções, podendo atuar como moléculas reguladoras em doenças cardiovasculares, neurodegenerativas, inflamatórias e imunológicas. Dos grupos marinhos que produzem peçonha encontram-se os cnidários, liberando-o através de estruturas conhecidas como cnidócitos. Neste contexto, este projeto utilizou técnicas de transcriptômica e peptidômica, para caracterização de transcritos e peptídeos de uma espécie de anêmona marinha amplamente distribuída pela costa brasileira: a Bunodosoma caissarum (B. caissarum). As análises de transcriptoma realizadas até o momento resultaram na anotação de 23.444 genes, dos quais foram identificadas 48 toxinas produzidas por espécies pertencentes aos cnidários. Adicionalmente, 15 destas toxinas foram confirmadas por experimentos de proteômica do muco, sendo três previamente descritas em B. caissarum. Os dados de espectrometria de massas integrados à transcriptoma resultaram na identificação de 2102 sequências peptídicas. Esse trabalho, portanto, auxiliou no enriquecimento de banco de dados, passo inicial para futura investigação de moléculas com potencial farmacológico.
Tentacle transcriptome and peptidome of Bunodosoma caissarum CORRÊA, 1964
Keywords: Anêmonas; Transcriptoma; Peptidoma; Espectrometria de massas